Toward Long-Distance Underwater Wireless Optical Communication Based on A High-Sensitivity Single Photon Avalanche Diode - Honglan Chen; Xinwei Chen; Jie Lu; Xiaoyan Liu; Jiarong Shi; Lirong Zheng; Ran Liu; Xiaolin Zhou; Pengfei Tian (IEEE Photonics Journal, 2020)
In this study, we built a single photon avalanche diode (SPAD) receiver based underwater wireless optical communication (UWOC) system. The bit error rate (BER) and signal-to-noise ratio (SNR) performance of UWOC with different distances and data transmission rates were obtained. Based on the water attenuation coefficient of 0.12 m−1, a series of neutral density (ND) filters were exploited to attenuate the light output power from the blue laser diode (LD) to simulate the long distance UWOC. The maximum estimated distances of 144 m and 117 m with corresponding BERs of 1.89 × 10−3 and 5.31 × 10−4 at data transmission rates of 500 bps and 2 Mbps were acquired in UWOC system using on-off keying (OOK) modulation scheme, respectively. Furthermore, we compared the differences between free-space and underwater channels, and a divergence angle of ∼1.02 mrad was measured experimentally at a distance of 50 m in the free space. The long UWOC distances obtained in this study partly benefit from high sensitivity SPAD, the small laser divergence angle and low light attenuation. This study provides an approach to achieve long distance UWOC using SPAD.